Application of Computer Simulation in Exploring the Effects of Achyranthis Bidentatae Radix on Simultaneously Treating Wei Syndrome and Bi Syndrome of Osteoarthritis - Chunsong ZHENG; Hongzhi YE; Jinxia YE; Changlong FU (康复学报)
Objective:To explore the pharmacodynamic material basis, action targets and modes of Achyranthis Bidentatae Radix (Niuxi in Chinese) on the simultaneous treatment of Wei syndrome and Bi syndrome in osteoarthritis (OA) from the molecular level.Methods:①Seventy-three chemical components of Niuxi were retrieved from the databases of China National Knowledge Infrastructure (CNKI) and PubMed, and to built molecular dataset of Niuxi. Meanwhile, three drugs related to articular cartilage proteoglycan synthesis stimulation (the treatment for Wei syndrome) and twenty-eight drugs related to anti-inflammation analgesia (the treatment for Bi syndrome) on OA were searched from the DrugBank database, and their corresponding molecular datasets of treating Wei syndrome and Bi syndrome were also built. Based on the platforms of quantitative structure-activity relationship and principal component analysis, the distributions of the above datasets were analyzed in the chemical space.②Matrix metalloproteinase-1 (MMP-1), matrix metalloproteinase-3 (MMP-3), and transforming growth factor beta-1 (TGF-β1) were chosen as the targets of treating Wei Syndrome of OA, while interleukine-1 beta (IL-1β), interleukine-6 (IL-6), tumor necrosis factor-alpha (TNF-α) were chosen as the targets of treating Bi syndrome of OA. The platforms of molecular docking and biological network were used to study the interactions between the Niuxi compounds and above targets, and Niuxi compound-target networks related to the treatment of Wei syndrome and Bi syndrome were constructed to analyze the pharmacodynamic material basis, action targets and modes of Niuxi in the therapy of OA.Results:①Comparison of the chemical space distributions between molecular datasets of Niuxi and drugs indicated that the chemical space distributions of the former were more diverse than those of the latter, and the former were the same, or close to the latter with the treatment of Wei syndrome at the back of chemical space, while the former were the same, or close to the latter with the treatment of Bi syndrome at the bottom back corner of chemical space. These revealed the possible effects of Niuxi on Wei syndrome and Bi syndrome of OA.②The compound-target networks showed that the main pharmacodynamic material basis of Niuxi contained saponins, phytosterones, flavonoids and alkaloids. Meanwhile, the Niuxi compound numbers of treating Bi syndrome and Wei syndrome were thirty-seven and twenty-six, respectively. Among them, twenty compounds could simultaneously treating Bi syndrome and Wei syndrome of OA. The maximum number of targets interacting with them was six. Furthermore, in the compound-target network of Niuxi in treating Bi syndrome of OA, the key compound nodes of Niuxi were puerarin, baicalin, quercetin-3-O-rutinose and kaempferol-3-O-glucoside, which belonged to flavonoids, and the key target nodes were IL-1β and TNF-α. In the compound-target network of Niuxi in treating Wei syndrome of OA, the key compound node of Niuxi was baicalin, which belonged to flavonoids, and the key target node was MMP-1.Conclusion:Computer simulation intuitively showed the multi-target effects of Niuxi in simultaneously treating Wei syndrome and Bi syndrome of OA through the modes like promiscuous drug and combination drug. This could provide a basis for Niuxi therapeutic for OA and new drug development from Niuxi.